Effect of vitamin D supplementation on pegylated interferon/ribavirin therapy for chronic hepatitis C genotype 1b: a randomized controlled trial. Issue 5 (30th July 2013) - Yokoyama, S.; Takahashi, S.; Kawakami, Y.; Hayes, C. N.; Kohno, H.; Kohno, H.; Tsuji, K.; Aisaka, Y.; Kira, S.; Yamashina, K.; Nonaka, M.; Moriya, T.; et al.
Summary Chronic HCV–infected patients tend to have vitamin D deficiency, suggesting that vitamin D supplementation may enhance the efficacy of treatment with pegylated interferon (PEG‐IFN) and ribavirin (RBV). We therefore assessed the effects of vitamin D supplementation on viral response to PEG‐IFN/RBV. Eighty‐four patients with HCV genotype 1b were randomized, 42 to oral vitamin D supplementation (1000 IU/day) and 42 to nonsupplementation (control), from week 8 to the end of PEG‐IFN/RBV therapy. The primary end point was undetectable HCV RNA at week 24 (viral response [VR]). VR rate at week 24 was significantly higher in the vitamin D than in the control group (78.6% vs 54.8% P = 0.037). Adverse events were similar in both groups. When patients were subdivided by IL28B SNP rs8099917 genotype, those with the TT genotype group showed a significantly higher VR rate at week 24 with than without vitamin D supplementation (86.2% vs 63.3% vs P = 0.044). Although patients with the TG/GG genotype, who were relatively resistant to PEG‐IFN treatment, had similar VR rates at week 24 with and without vitamin D supplementation, the decline in viral load from week 8 to week 24 was significantly greater with than without vitamin D supplementation. Multivariate analysis showed that rs8099917 genotype and vitamin D supplementation contributed significantly to VR at week 24. SVR rates were similar in the vitamin D and control groups [64.3% (27/42) vs 50% (21/42), P = 0.19]. Vitamin D supplementation may enhance the effects of PEG‐IFN/RBV in HCV genotype 1b–infected patients.